Hydrogen production in a semi‐single‐chamber microbial electrolysis cell based on anode encapsulated in a dialysis bag. (20th July 2021) - Rozenfeld, Shmuel; Gandu, Bharath; Hirsch, Lea Ouaknin; Dubrovin, Irina; Schechter, Alex; Cahan, Rivka
Summary: This study focuses on a semi‐single‐chamber microbial electrolysis cell (MEC) based on an anode made of carbon cloth (CCp) combined with stainless‐steel (SS) and encapsulated in a dialysis bag with different molecular weight cut‐offs of 2, 14, and 50 kDa (D2‐, D14‐, and D50‐COMBp, respectively). The encapsulated anode was inoculated with Geobacter sulfurreducens in a small volume directly into the dialysis bag. While the MEC with the non‐encapsulated anode was inoculated into the main chamber volume. The hydrogen evolution rates obtained in the MECs based on D2‐COMBp, D14‐COMBp, and D50‐COMBp anodes were 0.134 ± 0.005, 0.144 ± 0.014, and 0.160 ± 0.009 m 3 m −2 d −1, respectively; while the COMBp led to only 0.122 ± 0.004 m 3 m −2 d −1 . When the MEC utilizing D50‐COMBp was fed with wastewater, the current density was only 12.4 ± 0.21 A m −2, compared to feeding with acetate (15.7 ± 0.63 A m −2 ). The encapsulated anode in the presence of wastewater included 70% of G. sulfurreducens, while the non‐encapsulated included only 58%. Abstract : Left: A semi‐single‐chamber MEC based on anode material encapsulated in a dialysis bag. Right: Relative bacterial distribution with respect to genus: in the biofilm of the encapsulated anode when the MEC was fed with acetate (A) and wastewater (B); the non‐encapsulation anode in the MEC, which was fed with wastewater (C); and the planktonic bacteria (D) in the MEC utilizing the non‐encapsulation anode.